Study and improvement of a trapezium-metacarpal prosthesis in relationship with the bone remodeling phenomena - Lamblin, Daniel; Guerlement, Guy; Parys, Laurent Van; Datoussaïd, Sélim (Computer Assisted Methods in Engineering and Science, 2022)
Simulation of the long term behavior of a metacarpal bone with a prosthesis is presented with the help of an evolutive 3D finite element model taking into account "the stress shielding" phenomena. The same model allows to improve the shape of the prosthesis.